2008
DOI: 10.1017/s0007114507901221
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of fructo-oligosaccharide reduces 2,4-dinitrofluorobenzene-induced contact hypersensitivity in mice

Abstract: Strategies to manipulate the intestinal microbiota have been considered to promote immune health. The aim of the present study was to examine whether fructo-oligosaccharide, a typical prebiotic, could suppress antigen-specific skin inflammation by favourably changing the population of intestinal microbiota. Female BALB/c mice were fed a synthetic diet with or without fructo-oligosaccharide supplementation for 3 weeks and were then epicutaneously immunised with 2,4-dinitrofluorobenzene. Afterwards, mice continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 45 publications
4
37
0
1
Order By: Relevance
“…2). The results are consistent with our previous studies (13,14,25) and suggest that dietary FOS influenced the composition of gut microbiota. However, both conventional culture analysis and 16S rRNA gene-based analysis showed no detectable levels of bifidobacteria in the gut of NC/Nga mice (data not shown).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…2). The results are consistent with our previous studies (13,14,25) and suggest that dietary FOS influenced the composition of gut microbiota. However, both conventional culture analysis and 16S rRNA gene-based analysis showed no detectable levels of bifidobacteria in the gut of NC/Nga mice (data not shown).…”
Section: Resultssupporting
confidence: 93%
“…We previously observed that dietary FOS reduced DNFB-induced CHS in BALB/c mice ( 25 ). In the present study, experiment 1 tested whether NC/Nga mice also showed the reduction of DNFB-induced CHS by dietary FOS.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Amplification and detection of fecal DNA were performed with a Smart Cycler II (Cepheid, Sunnyvale, CA), as described previously. 31) Briefly, a Lactobacillus genus-specific primer pair (forward, TGG AAA CAG (A/G)TG CTA ATA CCG; reverse, GTC CAT TGT GGA AGA TTC CC) 32) was used. Real-time PCR was performed in a reaction volume of 25 ml, containing 12.…”
Section: Methodsmentioning
confidence: 99%
“…15) Vos et al reported that consumption of a mixture of long-chain FOS and short-chain GOS suppressed airway hyperresponsiveness and infiltration of inflammatory cells in an OVA-induced allergic asthma model of BALB/c mice. 16) In addition, we have reported that dietary FOS reduced 2,4-dinitrofluorobenzeneinduced contact hypersensitivity in BALB/c mice, 17) but the mechanisms of the anti-allergic effect of dietary indigestible oligosaccharides are not fully understood.…”
mentioning
confidence: 99%